Influence of ABCB1 C3435T and C1236T gene polymorphisms on tumour response to docetaxel‐based neo‐adjuvant chemotherapy in locally advanced breast cancer patients of South India. (13th January 2019) - Priyadarshini, Rekha; Raj, Gerard Marshall; Kayal, Smita; Ramesh, Ananthakrishnan; Shewade, Deepak Gopal
Summary: What is known and objective: Variable response to docetaxel‐based neo‐adjuvant chemotherapy (NACT) in breast cancer patients had been reported. Genetic polymorphisms in the ABCB1 gene coding for the efflux transporter MDR1 (P‐glycoprotein, P‐gp) could result in altered tumour response. Hence, this study was proposed to assess the effect of single nucleotide polymorphisms (SNPs) of ABCB1 gene on tumour response in locally advanced breast cancer patients (LABC) of South India who have a distinct genetic makeup. Methods: Out of 162 LABC patients recruited, 129 patients were included for the final analysis. DNA was extracted by "phenol‐chloroform extraction method" from the WBCs, and genotyping for SNPs rs1045642 (C3435T) and rs1128503 (C1236T) in ABCB1 gene was performed with real‐time PCR system using validated TaqMan ® SNP genotyping assay method. Tumour response was assessed by RECIST criteria based on the MRIs taken before and after completion of four cycles of docetaxel therapy. Results and discussion: A total of 102 (79.1%) patients were found to be responders and 27 (20.9%) patients were found to be non‐responders to docetaxel therapy. Patients with "CT/TT" genotypes (response rate: 83.3%) of ABCB1 (C1236T) gene showed better tumour response than those with "CC" genotype (response rate: 16.6%) [OR = 2.94 (CI: 1.15‐7.52); P  =   0.03]. However, on performing binary logistic regression, neither the studied SNPs nor the non‐genetic factors like age, BMI, postmenopausal status, laterality of the tumour, ER status, PR status and Her‐2/neu status were found to be associated with tumour response to docetaxel ( P  >   0.05). What is new and conclusion: The tumour response to docetaxel was significantly influenced by the SNP C1236T of ABCB1 gene coding for the P‐gp. However, when adjusted for other non‐genetic factors, neither of the ABCB1 variants were found to be associated with tumour response to docetaxel‐based NACT in LABC patients of South India. Abstract : The tumour response to docetaxel was significantly associated with the SNP C1236T (rs1128503) of ABCB1 gene coding for the MDR1 transporter or P‐glycoprotein. Patients with the "CT/TT" genotype displayed comparatively better tumour response than those with the "CC" genotype. However, when adjusted for other factors like age, BMI, postmenopausal status, laterality, ER status, PR status and Her‐2/neu status neither of the ABCB1 variants were found to be associated with tumour response to docetaxel in LABC patients of South India.